Chemically Modified Graphene: The Influence of Structural Properties on the Assessment of Antioxidant Capacity. Issue 33 (1st July 2015) - Hui, Kai Hwee; Pumera, Martin; Bonanni, Alessandra
Abstract Graphene materials obtained by different synthetic routes possess dissimilar amount of defects and surface functionalities, which can influence their electrochemical performance towards the detection of electroactive probes. Oxygen‐containing groups can be either detrimental to the heterogeneous charge transfer or promote favorable interactions between the graphene surface and the analyte of interest, depending on the structure of the latter. Here, we compared three chemically modified graphenes, obtained by various procedures and carrying different amounts of oxygen functionalities, for the detection of standard gallic acid, a compound commonly used as an index of the antioxidant capacity of food and beverages. We found that electrochemically reduced graphene provided the best electrochemical performance in terms of calibration sensitivity, selectivity, and linearity of response. Our findings are important in order to understand the suitability of graphene platforms for the assessment of food quality.